Effects of wave exposure on the abundance and composition of amphipod and tanaidacean assemblages inhabiting intertidal coralline algae. (11th August 2015) - Bueno, M.; Dena-Silva, S.A.; Flores, A.A.V.; Leite, F.P.P.
Abstract : Peracarid crustaceans are an important component of the vagile fauna associated with coralline algal beds, which often characterize the infralittoral fringe of tropical rocky shores. Among other variables affecting faunal assemblages, sedimentation, food supply and oxygen concentration within mats or turfs of coralline algae may greatly depend on the exposure to waves. In this study, peracarid assemblages were compared at replicated rocky shores within different levels of wave exposure, along a coastline in south-eastern Brazil. Overall amphipod diversity (11 species) was much higher than tanaidacean diversity (two species). Correlation analyses did not support any biological interactions between amphipods and tanaidaceans. Habitat complexity, while apparently limiting amphipod populations, did not affect tanaidaceans at a local scale. Amphipod abundance, not assemblage structure, was positively affected by wave exposure, probably improving oxygen concentration levels and renewal of food resources. Rather than abundance, which remains fairly stable, exposure to waves determined species identity in tanaidaceans, with Zeuxo coralensis found at exposed shores and Leptochelia aff. dubia found at sheltered shores, except for two L. aff. dubia individuals found at one of the exposed sites. Differences in the supply of sediment and the ability of these species in manipulating grains for tube building may explain such a striking pattern.